ANALISIS PENGARUH VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN PERAIH PENGHARGAAN ANNUAL REPORTING AWARD (ARA)TAHUN 2014 - Firmansyah, Hamdan; Hadijono, Sri (Universitas 17 Agustus 1945 Surabaya, 2016)
Participation in the Annual Report Award 2014 is a manifestation of Good Corporate Governance and can be a means for companies to obtain input from various sources on how well the annual report and at the same time strengthen the company's presence in the industrial communities. The purpose of this study was to determine the effect of the volume of stock trading on stock return on the award-winning Annual Report Award (ARA) companies in 2014. It also determined empirically whether there were differences in the volume of stock trading and stock returns before and after the announcement of the Annual Report Award ( ARA) in 2014. The approach and type of this research was quantitative descriptive. The population in this study were the companies that became the winner of the award Annual Report Award (ARA) year 2014. The sample was the company went public listed on the Indonesia Stock Exchange (BEI) award recipient Annual Report Award (ARA) in 2014, as many as 11 companies. Data used by the author was secondary data, where the data was taken in the form of the annual closing price of those companies. As the announcement of ARA held on October 16, 2014, the period of this study conducted over 10 days, five days before the announcement (D - 5), and 5 days after the announcement (D + 5). The results showed that the t test for variable stock trading volume on stock returns had t count of -1.229 with a significant level of 0.222 where the sig value is greater than 0.05 (0.222> 0.05), it can be concluded that there is no significant effect on the correlation between the volume of stock trading on stock returns of the companies. The average mean trading volume of shares of the companies prior to the announcement was 0.0003782 compared to 0.0003703, after the announcement. It showed a decreasing of 0.00000795. It can be concluded that there were differences in the volume of stock trading company's award-winning Annual Report Award (ARA) in 2014 before and after the date announcement. The average stock return prior to the announcement was 0.0006284 and the average stock return after the announcement was 0.0044502. It increased by 0.0038218. It was concluded that there were no differences in stock returns of ARA award-winning companies in 2014 before and after the date of announcementKeywords: Good Corporate Governance, Annual Report Award, the volume of stock trading, stock returns